2009
DOI: 10.1063/1.3125262
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-driven slug motion in capillary tubes

Abstract: The velocity of a liquid slug falling in a capillary tube is lower than predicted for Poiseuille flow due to presence of menisci, whose shapes are determined by the complex interplay of capillary, viscous, and gravitational forces. Due to the presence of menisci, a capillary pressure proportional to surface curvature acts on the slug and streamlines are bent close to the interface, resulting in enhanced viscous dissipation at the wedges. To determine the origin of drag-force increase relative to Poiseuille flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…(1), (7), and (10)). The method has proven able to numerically simulate jet breakup and splashing [33,32,41] and to deal with the contact angle in a rather natural way, capturing all relevant mechanisms, which include hysteresis of the contact angle and film flow [23,26,41]. It consists of three main ingredients: an appropriate model of surface tension; a technique to advect the fluid-function that controls the numerical diffusion; and a Navier-Stokes solver.…”
Section: The Volume Of Fluid (Vof) Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(1), (7), and (10)). The method has proven able to numerically simulate jet breakup and splashing [33,32,41] and to deal with the contact angle in a rather natural way, capturing all relevant mechanisms, which include hysteresis of the contact angle and film flow [23,26,41]. It consists of three main ingredients: an appropriate model of surface tension; a technique to advect the fluid-function that controls the numerical diffusion; and a Navier-Stokes solver.…”
Section: The Volume Of Fluid (Vof) Methodsmentioning
confidence: 99%
“…(13). Note that this does not imply that the curvature of the interface remains constant if the interface is moving: the normal vector is fixed only on the faces adjacent to the solid whereas the velocity field can deform the interface in the other cells (see also [26]). The dynamic effects associated with the constant contact angle are therefore taken into account.…”
Section: The Continuum Surface Force (Csf) Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…1 at z > f 0 ) soil is dry (or more accurately, the immobile moisture content is at an irreducible value), as discussed in Kacimov and Obnosov (2013), Lunati and Or (2009), Ali et al (2013), Assouline (2013) and Valiantzas (2010). In this sense, the GA model is similar to the Washburn-Lukas (WL) model on the level of capillary channels (see, e.g., Lunati and Or 2009;Hilpert and Glantz 2013) and both models-by solving a Cauchy problem for a nonlinear ODE-mathematically predict a finite (although, generally speaking, discontinuous) speed of front/meniscus propagation through a dry soil or empty capillary tube. As numerous experiments and field studies showed (see, e.g., Siemens et al 2013), the GA fronts propagating downward through a practically dry soil leave a "tail" of air-filled pore space at z > d in our Fig.…”
Section: Pore-scale Modelmentioning
confidence: 97%